THE EFFECT OF COVID-19, WORKING FROM HOME, AND TIME BUDGET PRESSURE ON THE QUALITY OF AUDITOR PERFORMANCE - Minaryanti, Annisa Adha; Suraida, Ida; Dewi, Ratu Ratna; Akhir, Sekar Nisaul (JURNAL AKUNTANSI FINANCIAL STIE SULTAN AGUNG, 2023)
The purpose of this study is to determine the extent of the impact of Covid-19 conditions, work-from-home practices, and time-budget pressure on quality of audit performance in 10 audit firms in Bandung City area. Covid-19 situation, home office implementation and time budget pressure situation as independent variables, and auditor performance as dependent variables. The research approach used in this study is descriptive analysis and validation based on primary data. The population of this study was all accountants from 10 accounting firms in Bandung. The number of samples collected was 67 judges. Based on the results of the research conducted, we find that the Covid-19 condition has a significant impact on the quality of auditor performance, with a contribution of 22%. For 21%, working from home has a significant impact on the quality of an auditor's performance. Time pressure has a significant negative impact on the examiner's performance with her 15.9%. This means that the higher the time pressure, the lower the quality of the exam.Keywords: Covid-19, Work From Home, Time Budget Pressure and Quality of Audit Performance